2012
DOI: 10.1083/jcb1965oia7
|View full text |Cite
|
Sign up to set email alerts
|

An extra allele of Chk1 limits oncogene-induced replicative stress and promotes transformation

Abstract: Replicative stress (RS) is a type of endogenous DNA damage that cells suffer every time they duplicate their genomes, and which is further boosted by oncogenes. In mammals, the RS response (RSR) is coordinated by ATR and Chk1 kinases. We sought to develop a mammalian organism that is selectively protected from RS. To this end, mice carrying an extra copy of the Chk1 gene were generated. In vitro, Chk1 transgenic cells are protected from RS-inducing agents. Moreover, an extra Chk1 allele prolongs the survival o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 27 publications
8
38
0
Order By: Relevance
“…Of note, the addition of an extra allele of Chk1 has even been found to promote Ras-or E1A-mediated transformation more efficiently in comparison to such transformation of wild-type littermates (Lopez-Contreras et al, 2012), suggesting that the ATR-Chk1 axis has a pro-malignant transformation role.…”
Section: Box 1 Relevance Of Atm and Atr Signaling In Cancermentioning
confidence: 99%
“…Of note, the addition of an extra allele of Chk1 has even been found to promote Ras-or E1A-mediated transformation more efficiently in comparison to such transformation of wild-type littermates (Lopez-Contreras et al, 2012), suggesting that the ATR-Chk1 axis has a pro-malignant transformation role.…”
Section: Box 1 Relevance Of Atm and Atr Signaling In Cancermentioning
confidence: 99%
“…44), checkpoint kinase Chk1 could be the most promising candidate to be targeted for prosenescence therapy, as Chk1 inhibitors are already in clinical trials (55). We recently demonstrated that inhibition of constitutive Chk1 activity in various cancer cell lines reduces CIP2A expression resulting in PP2A reactivation and potent inhibition of malignant cell growth (67), whereas increased Chk1 expression was shown to protect against oncogene-induced replicative stress and to promote transformation (68). Finally, as different PP2A complexes mediate senescence induction and regulate E2F1 (49), testing of efficacy of small-molecule activators of PP2A (17,47) as novel prosenescence therapeutic agents might be warranted.…”
Section: Senescence Induction In Cancer Cells With Compromised P53 Fumentioning
confidence: 99%
“…2C). This strategy, in contrast to classic transgenesis using plasmids harboring cDNA, has been proven successful for generating animals with increased activity of genes that are otherwise deleterious when aberrantly overexpressed, such as Chk1 or Tp53 (Garcia-Cao et al 2002;Lopez-Contreras et al 2012).…”
Section: Generation Of a Mouse Model With Increased Rrm2 Levelsmentioning
confidence: 99%
“…2C). This strategy, in contrast to classic transgenesis using plasmids harboring cDNA, has been proven successful for generating animals with increased activity of genes that are otherwise deleterious when aberrantly overexpressed, such as Chk1 or Tp53 (Garcia-Cao et al 2002;Lopez-Contreras et al 2012).Transgenic lines were identified by Southern blotting, and the integration site was subsequently mapped by inverse PCR. We selected one line (Rrm2 TG ) carrying several alleles integrated in tandem (Fig.…”
mentioning
confidence: 99%